2018
DOI: 10.1111/jcmm.14061
|View full text |Cite
|
Sign up to set email alerts
|

ADIPOQ,KCNJ11 and TCF7L2 polymorphisms in type 2 diabetes in Kyrgyz population: A case‐control study

Abstract: The aim of this study was to ascertain the polymorphic markers profile of ADIPOQ,KCNJ11 and TCF7L2 genes in Kyrgyz population and to analyze the association of polymorphic markers and combinations of ADIPOQ gene's G276T locus, KCNJ11 gene's Glu23Lys locus and TCF7L2 gene's VS3C>T locus with type two diabetes (T2D) in Kyrgyz population. In this case‐control study, 114 T2D patients 109 non‐diabetic participants were genotyped using polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP). Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Substantial evidence demonstrate that T2DM can be attributed by lifestyle, environmental and genetic factors [5][6][7][8]. Although the etiology of T2DM is complex and needs further study, genetic factors have been identified to be an important cause, and an increasing number of candidate genes have been identified recent years [9,10]. Thus, investigating the candidate genes involved in the onset and development of T2DM may shed light on the molecular mechanisms underlying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence demonstrate that T2DM can be attributed by lifestyle, environmental and genetic factors [5][6][7][8]. Although the etiology of T2DM is complex and needs further study, genetic factors have been identified to be an important cause, and an increasing number of candidate genes have been identified recent years [9,10]. Thus, investigating the candidate genes involved in the onset and development of T2DM may shed light on the molecular mechanisms underlying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The data did not conform to the HWE test, and hence, these studies were excluded. In the Kyrgyz population [ 80 ], a correlation was established between the allele and heterozygous genotype of rs1501299 and T2DM. However, limited statistical data and inconformity with the HWE test led to the exclusion of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are varying reports of the association between T2DM and the rs5219 and rs5210 genotypes in KCNJ11 in different populations [11,[32][33][34][35][36][37][38][39]. Moreover, this association has yielded different results in the same population as well.…”
Section: Kcnj11 Kcnq1mentioning
confidence: 99%